Performance direction setting: a review on Malaysian development financial institutions - Shamsudin, Norazidah; Omar Mohammed, Mustafa; Azlinna Azizan, Noor; ., . (International Journal of Engineering and Technology, 2018)
Development Financial Institutions (DFIs) play an important roles in Malaysian economy. As a bank which been appointed prescribed under Development Financial Institutions Act (DFIA) 2002, Malaysian DFIs have to proceed its banking operation and concurrently carrying a mandate given by the government striving for socio-economic development. The DFIs advancement towards full-fledged Islamic entity and the mandate that they have carried out in promoting the public interest, leads to the research on reviewing the Malaysian DFIs performance direction setting. All six DFIs which prescribed under DFIA 2002 been taken as a scope of study. The content of vision and mission statement of the DFIs are analysed and classified into the Performance Measures based on Maqasid al-Shari’ah (PMMS) model. The objectives of the study are (1) to identify whether Malaysian DFIs currently have fully covered all three concepts and nine dimensions of Maqasid-al Shari’ah and (2) to analyze which concept and dimension have the most concentration. The result of the study could be as a reference for DFIs’ future direction setting in striving the mandate given in promotiong socio-economic development and at the same time fulfilling the Maqasid al-Shari’ah and been recognized as full-fledged Islamic financial institutions.